2018
DOI: 10.1155/2018/8329406
|View full text |Cite
|
Sign up to set email alerts
|

The Form of Waiting Time Distributions of Continuous Time Random Walk in Dead-End Pores

Abstract: Anomalous dispersion of solute in porous media can be explained by the power-law distribution of waiting time of solute particles. In this paper, we simulate the diffusion of nonreactive tracer in dead-end pores to explore the waiting time distributions. The distributions of waiting time in different dead-end pores show similar power-law decline at early time and transit to an exponential decline in the end. The transition time between these two decline modes increases with the lengths of dead-end pores. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The characteristics of the flow fields suggest that they are the bridges connecting the medium properties and the solute transport characteristics. It has been found that the mechanisms of many solute transport phenomena can be explained by analyzing the characteristics of the flow fields [38,39]. For example, previous studies have shown that the heterogeneity of a flow field has significant impacts on solute dilution.…”
Section: Mechanismmentioning
confidence: 99%
“…The characteristics of the flow fields suggest that they are the bridges connecting the medium properties and the solute transport characteristics. It has been found that the mechanisms of many solute transport phenomena can be explained by analyzing the characteristics of the flow fields [38,39]. For example, previous studies have shown that the heterogeneity of a flow field has significant impacts on solute dilution.…”
Section: Mechanismmentioning
confidence: 99%